2018
DOI: 10.1096/fj.201801294r
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for the directed motility of keratinocytes driven by electric fields

Abstract: Endogenous wound electric fields (EFs), an important and fundamental occurrence of wound healing, profoundly influence the directed migration of keratinocytes. Although numerous studies have unveiled the signals responsible for EF‐biased direction, the mechanisms by which EFs promote keratinocyte motility remains to be elucidated. In our study, EFs enhanced the directed migratory speed of keratinocytes by inducing autophagic activity, thereby facilitating skin barrier restoration. Initially, we found that elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…A growing body of literature indicates that autophagy is a central mechanism by which various factors promote the motility of keratinocytes (Yan et al, 2019). Previous studies reported that Fgf21 deficiency impairs autophagy in several tissues, including the liver and muscle.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of literature indicates that autophagy is a central mechanism by which various factors promote the motility of keratinocytes (Yan et al, 2019). Previous studies reported that Fgf21 deficiency impairs autophagy in several tissues, including the liver and muscle.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that autophagy is shown to be activated in response to glucose withdrawal via activation of PRKAA2/AMPK (protein kinase AMP-activated catalytic subunit alpha 2) and inactivation of MTOR [ 67 ]. Besides, directed migratory speed could be enhanced via inducing autophagic activity in keratinocytes driven by electric fields [ 68 ]. A recent study has also revealed the critical role of keratinocyte autophagy in facilitating wound healing via regulating CCL2 (C-C motif chemokine ligand 2) expression in a mouse model [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One can build a suitable microenvironment for wound healing, one can load with stem cells and various healing promoting factors (growth factors, exosomes, etc. ), novel functional and intelligent biomimetic wound repair materials with anti-infective agents (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Vigorously Facilitating Specialized Technologymentioning
confidence: 99%